State Farm‐to‐School Laws Influence the Availability of Fruits and Vegetables in School Lunches at US Public Elementary Schools. (May 2014) - Nicholson, Lisa; Turner, Lindsey; Schneider, Linda; Chriqui, Jamie; Chaloupka, Frank
ABSTRACT BACKGROUND State laws and farm‐to‐school programs (FTSPs) have the potential to increase fruit and vegetable (FV) availability in school meals. This study examined whether FV were more available in public elementary school lunches in states with a law requiring/encouraging FTSPs or with a locally grown‐related law, and whether the relationship between state laws and FV availability could be explained by schools opting for FTSPs. METHODS A pooled, cross‐sectional analysis linked a nationally representative sample of public elementary schools with state laws. A series of multivariate logistic regressions, controlling for school‐level demographics were performed according to mediation analysis procedures for dichotomous outcomes. RESULTS Roughly 50% of schools reported FV availability in school lunches on most days of the week. Schools with the highest FV availability (70.6%) were in states with laws and schools with FTSPs. State laws requiring/encouraging FTSPs were significantly associated with increased FV availability in schools and a significant percentage (13%) of this relationship was mediated by schools having FTSPs. CONCLUSIONS Because state farm‐to‐school laws are associated with significantly higher FV availability in schools—through FTSPs, as well as independently—enacting more state legislation may facilitate increased FTSP participation by schools and increased FV availability in school meals.